Geological development of eastern Humber and western Dunnage zones: Corner Brook - Glover Island region, Newfoundland - Cawood, Peter Anthony; vanGool, J A M; Dunning, G R (1996)
The Corner Brook-Glover Island region records the development of the internal domain of the Humber Zone and its relationship to the adjoining external domain and Dunnage Zone. The region preserves both the Laurentian margin basement-cover contact and the siliciclastic-carbonate transition within the cover sequence. Precambrian Grenville basement of the Corner Brook Lake Complex is the oldest lithostratigraphic unit and yielded a U/Pb zircon age of 1510 +/- 6 Ma. Three main lithostratigraphic assemblages overlie basement: silicic and mafic igneous rocks of the Lady Slipper Pluton which yielded a U/Pb zircon age of 555(-5)(+3) Ma; siliciclastic lithologies which include the South Brook and Summerside formations; and carbonate-dominated sequences with elastic incursions which include the Port au Port, St. George, and Table Head groups, and the Breeches Pond, Irishtown, and Pinchgut formations. Dunnage Zone units include plutonic ultramafic to mafic rocks of the Grand Lake Complex, dated by U/Pb zircon from trondhjemite at 490 +/- 4 Ma, volcanic and epiclastic rocks of the Glover Island Formation, and the Matthews Brook Serpentinite, the latter restricted to fault slivers within the Humber Zone sequence. The deformed Glover Island Granodiorite intrudes the Dunnage Zone rocks on Glover Island and is dated by U/Pb zircon and titanite at 440 +/- 2 Ma. Little deformed Carboniferous sedimentary rocks unconformably overlie both Humber Zone and Dunnage Zone rock units. Timing of regional deformation and peak amphibolite-facies metamorphism in the eastern Humber Zone is constrained by isotopic data to the Early Silurian. In the Dunnage Zone, shear zones and foliation development both pre- and postdate the age of the Glover Island Granodiorite, with the later possibly temporally equivalent to deformation in the Humber Zone. Final juxtaposition of the two zones occurred during Carboniferous movement of the Cabot Fault.